Online Personalized Normative Alcohol Feedback for Parents of First Year College Students - Napper, Lucy E. (Psychol Addict Behav, 2016)
This study examined the efficacy of a personalized normative feedback (PNF) alcohol intervention for parents of students transitioning into college. A sample of 399 parent-student dyads were recruited to take part in the intervention during the summer prior to matriculation. Parents were randomly assigned to receive either normative feedback regarding student drinking and other college parents’ alcohol-related communication or general college health norm information. Students completed measures of alcohol use, alcohol consequences, and parent-child alcohol-specific communication both 1- and 6-months after matriculation. The results indicated that in comparison to the control condition parents who received PNF reported immediate changes in their perceptions of other parents’ behaviors; however, these changes in parent perceived norms did not translate into long-term changes in student drinking behaviors or parent-child communication. Findings highlight the need to consider content beyond normative feedback for parent based alcohol intervention.